SILICA SUPPORTED PERCHLORIC ACID (HCLO4-SIO2) AS ECOFRIENDLY REUSABLE CATALYSTS FOR GREEN SYNTHESIS OF TETRAHYDROBENZO[B]PYRAN DERIVATIVES BY GRINDING METHOD (International Journal of Food and Nutritional Sciences, 2022)
Silica supported perchloric acid (HClO4-SiO2) is explored as reusable catalyst for the synthesis of 4H-benzo[b]pyran derivatives from one-pot three component condensation of aldehydes, dimedone and malononitrile by using grinding method. This method provides several advantages including environmental friendliness, short reaction times, high yields and a simple work-up procedure.